Personalized Medicine with a Nanochemistry Twist Nanomedicine - Pan, Dipanjan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Barriers in Nanomedicine: The Importance of Defined Chemistry and Engineering Approaches for Clinical Translation --Huei-Huei Chang, Shaneen Braswell, Jonathan George, Mark Gryka, Sumin Kim, Nicolas Kolmodin, Manu Kumar, Benjamin Seadler, Oluwayemisi Sonoiki, and Dipanjan Pan Nanoscopic Agents in a Physiological Environment: The Importance of Understanding Their Characteristics --Victoria Sherwood, Desirè Di Silvio, and Francesca Baldelli Bombelli Rational Design of Multifunctional Nanoscale Self-Assembled Soft Materials for Biomedical Delivery Application --Shrinivas Venkataraman Multimodal Imaging and Theranostic Application of Disease-Directed Agents --Joseph Caffarini, Nathan Kelleher, Christian C. Konopka, Madeline Mazurek, Anuradha Nandyala, Dwani Patel, Stephanie Slania, Sheryl Wang, Ravi Chandra Yada, and Dipanjan Pan Nano-Enabled Delivery of Intracellular Therapeutics -- Fatemeh Ostadhossein, Enrique Alejandro Daza, Daniel Frankowski, Drew Goatz, Molly Imgruet, Joseph Kus, Ryan Lake, Mallika Modak, Nick Olsen, Aaron Schwartz-Duval, Alyssa Zimmer, Nicholas Kolmodin and Dipanjan Pan Personalized Medicine: Where Do We Go from Here?--Dipanjan Pan .
Barriers in Nanomedicine: The Importance of Defined Chemistry and Engineering Approaches for Clinical Translation -- Nanoscopic agents in a physiological environment: the importance of understanding their behavior -- Rational design and chemical challenges of supra-molecular assemblies of soft materials for biomedical delivery application -- Multimodal Imaging and Theranostic Application of Disease-directed Agents -- Nano-enabled Delivery of Intracellular Therapeutics -- Personalized Medicine: Where do we go from here?.
Keywords: Medicinal chemistry; Medicinal Chemistry